Potent Heterogeneous Catalyst for Low Temperature Selective Oxidation of Cyclohexanol by Molecular Oxygen - Haroon ur Rashid; M. Sohail Ahmad; Mohammad Sadiq; Razia Aman (Journal of Chemistry)
Platinum supported on zirconium dioxide catalyst was prepared by standard method and characterized by SEM, EDX, XRD, BET surface area and pore size analyzer, and FT-IR. The catalyst was screened for its catalytic activity in a model reaction, selective oxidation of cyclohexanol. The only one major product, cyclohexanone 31%, with 99.8% selectivity was obtained. Experimental data was analyzed through different kinetic models and we deduced that the reaction follows Langmuir-Hinshelwood mechanism. The apparent activation energy for the model reaction was calculated as 45 kJ/mole. The catalyst was regenerated several times with same efficiency.